2012
DOI: 10.1523/jneurosci.1643-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Suppression of Inositol 1,4,5-Triphosphate Receptor-Mediated Calcium Signaling in Cerebellar Purkinje Cells Alleviates Pathological Phenotype in Spinocerebellar Ataxia 2 Mice

Abstract: Spinocerebellar ataxia 2 (SCA2) is a neurodegenerative disorder characterized by progressive ataxia. SCA2 results from a polyglutamine (polyQ) expansion in the cytosolic protein ataxin-2 (Atx2). Cerebellar Purkine cells (PC) are primarily affected in SCA2, but the cause of PC dysfunction and death in SCA2 is poorly understood. In previous studies, we reported that mutant but not wild type Atx2 specifically binds the inositol 1,4,5-trisphosphate receptor (InsP3R) and increases its sensitivity to activation by I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
124
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(147 citation statements)
references
References 46 publications
21
124
1
1
Order By: Relevance
“…In both SCA2 and SCA3, the polyQ-expanded form of the protein binds to the IP 3 receptor and increases IP 3 -mediated calcium release [106,107]. Furthermore, chronic suppression of IP 3 signaling in vivo reduces neuronal dysfunction and cell death in a transgenic mouse model of SCA2 [108] and SCA3 [106]. Taken together, these data support a role for increased IP 3 -mediated calcium release in the pathogenesis of SCA2 and SCA3.…”
Section: Pathologic Calcium Handling In Polyq Disordersmentioning
confidence: 65%
“…In both SCA2 and SCA3, the polyQ-expanded form of the protein binds to the IP 3 receptor and increases IP 3 -mediated calcium release [106,107]. Furthermore, chronic suppression of IP 3 signaling in vivo reduces neuronal dysfunction and cell death in a transgenic mouse model of SCA2 [108] and SCA3 [106]. Taken together, these data support a role for increased IP 3 -mediated calcium release in the pathogenesis of SCA2 and SCA3.…”
Section: Pathologic Calcium Handling In Polyq Disordersmentioning
confidence: 65%
“…In this regard, our proteomic screen also revealed that a significant number of mitochondrial proteins involved in the ETC complexes and the ATP synthase were downregulated in mutant PCs, thereby affecting bioenergetics and proper mitochondrial functioning. Additionally, it is well accepted that calcium signaling is impaired in SCA1, SCA2 and SCA3 (Brown and Loew, 2012;Halbach et al, 2016;Kasumu et al, 2012;Pellistri et al, 2013) and as mitochondria are the second most important calcium storage organelle, improper mitochondrial functioning can negatively impact calcium homeostasis and neuronal transmission (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…4) [90]. Patchclamp experiments on cerebellar slices showed that virus-mediated IP 3 phosphatase overexpression improved age-dependent impairment in the electrophysiological activity of SCA2 PCs.…”
Section: Spinocerebellar Ataxia Types 2 Andmentioning
confidence: 99%